지역난방 노후 축열조의 부식 건전성 평가 및 고찰 - 윤대호; Daeho Yun; 채호병; Hobyung Chae; 김희산; Heesan Kim; 김정구; Jung-gu Kim; 김우철; Woo Cheol Kim; 하태백; Tae Baek Ha; et al. (대한금속·재료학회지, 58(10), 2020)
The thermal storage tank in a district heating system is a component that stores excess heat during normal operation and releases the stored heat to increase the efficiency of the system, when the heat source is stopped or additional demands occur. Recently, an obsolete thermal storage tank was dismantled for the first time since it began operation 30 years ago. In this work, the corrosion integrity of the obsolete thermal storage tank was evaluated by examining its appearance, thickness thinning, corrosion products, microstructure, and mechanical properties. Samples were taken at various locations (roof, shell, bottom) of the thermal storage tank, which enabled diagnosis of the respective environmental degradations. Severe corrosion was found in the roof edge plate due to corrosion under the insulation, and exhibited thinning exceeding ~49% of the designed thickness. In this location, the ferrite-pearlite band structure disappeared and deteriorated microstructures, such as decarburization and spheroidized pearlite, were measured, which resulted in a ~27% decrease in hardness. The inner surfaces of the bottom and shell plate were well covered with a magnetite film, and the degradation of the microstructure and mechanical properties showed a permissible limit in terms of ASTM A285/ A516. In addition, no particular drop in hardness was found in the weld zone of each plate.